Silver-Catalyzed Efficient Synthesis of Vinylene Carbonate Derivatives from Carbon Dioxide - Ugajin, Rie; Kikuchi, Satoshi; Yamada, Tohru (Synlett, 2014)
It was found that the silver salt and base was an efficient catalytic system for the reaction of the secondary propargylic alcohol with carbon dioxide to afford various corresponding vinylene carbonate derivatives in good to high yields under mild conditions.
Keywords: alkynes; vinylene carbonates; carbon dioxide; silver; isomerization; Lewis acids